Plato and the world of sound - Tomás, Lia (2012)
In this article we intend to propose some relations between the concepts of Music and Philosophy in Plato. To this end, the tale Dans un monde sonore, by Victor Segalen will be used as a metaphor for these concepts. We also intend to assert that, for the philosopher, Music and also Philosophy both necessarily involve acts of hearing and thinking, in such a way that hearing is exercised in speeches of all sorts that involve a word-selection inciting more to thinking than to speaking.